2015
DOI: 10.11648/j.ajam.20150302.14
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in Porous Triangular Enclosure with a Circular Obstacle in Presence of Heat Generation

Abstract: The flow and heat transfer due to natural convection in a triangular enclosure filled with a fluid saturated porous medium with a circular body in presence of heat generation has been numerically analyzed. The bottom wall of the enclosure is heated at a constant temperature while the left and right inclined wall of the cavity is maintained at cold temperature. The cavity contains a circular body which is insulated. The governing equations are solved numerically subject to suitable boundary conditions by Galerk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Natural convective heat transfer characteristics in enclosures have a great significance in industrial applications such as solar collectors, thermal storage systems, cooling of nuclear reactors, etc. In past years, different methods were used to augment the heat transfer in enclosures such as using porous media [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and nanotechnology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The corrugated annulus is a type of enhanced heat transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convective heat transfer characteristics in enclosures have a great significance in industrial applications such as solar collectors, thermal storage systems, cooling of nuclear reactors, etc. In past years, different methods were used to augment the heat transfer in enclosures such as using porous media [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and nanotechnology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The corrugated annulus is a type of enhanced heat transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Applications include effective cooling system for electronic components, solar collectors, thermal storage system, nuclear reactors, etc. In recent years, there are many attempts from researchers using different methods to enhance the heat transfer rate using of porous media [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and nanotechnology . The present study has used the second method.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded by them due to the presence of the solid adiabatic strip, the lower portion of the cavity remains very cold compared to the upper portion. Chowdhury et al [5] performed natural convection in porous triangular enclosure with a circular obstacle in presence of heat generation. They observed that the fluid flow and temperature field strongly depend on the presence of the circular body obstructs the flow and temperature fields.…”
Section: Introductionmentioning
confidence: 99%